PENDAMPINGAN PEMBENTUKAN KELOMPOK BIDANG KEILMUAN (KBK) PADA PROGRAM STUDI ADMINISTRASI PUBLIK FISIP UNIVERSITAS MULAWARMAN - Dyah Kuntorini Dwi Angreni; Fajar Apriani (As-Sidanah, 2025)
There is still a need for a higher level of participation from lecturers in implementing the Tridharma of Higher Education to produce scholarly publications. One solution is to initiate the Public Administration Research and Development Team (TERPADU) to enhance scholarly publications, particularly for lecturers in the Public Administration study program at FISIP. The approach method used in this community partnership program includes AKPL Criteria, USG Analysis, and Fishbone Analysis to determine the priority issues and root causes of problems. Thus, TERPADU can become the smallest unit in the technical implementation and substance of research activities. Based on the research plan targets for new Public Administration (AP) lecturers over the next five years, there are three main focuses that reflect a commitment to the development of public administration knowledge.One lecturer plans to develop a theory in this field, which is essential to strengthen the academic foundation and contribute to the literature. Second, seven lecturers target publications in reputable international journals, reflecting an awareness of the importance of global visibility and credibility in the academic community; support from the institution through writing training and access to resources is crucial. Overall, the lecturers expect the institution to be more active in supporting research and community service activities, not only with proportional funding but also by creating a collaborative and innovative academic environment. With the right support, the Public Administration Study Program is expected to produce high-quality research and community service, relevant to the needs of society, and provide a significant contribution to social development and public policy.